Factors influencing ethical consumption behavior among Muslim household: an empirical research in Terengganu, Malaysia - Zubaidah Mohd Nasir; Mashitoh Yaacob; W. Syairah Hazwani W. Petera (Penerbit Universiti Kebangsaan Malaysia, 2021)
One of the factors that contribute seriously to the degradation of environmental quality is household waste. Hence, household participation in environmental conservation especially in consumption ethics such as pre-cycling, reusing and recycling towards household waste management should be discussed. Therefore, this paper aims to identify the influential factors that reinforcing ethical consumption behavior of Muslim households in one of the east coast states of Malaysia known as Terengganu. Survey method was employed to gain information on the influential factors of pre-cycling, reusing and recycling activities. The questionnaire was distributed to 328 respondents through simple random sampling methods. Validity and reliability of 29 items with five scales were tested statistically. Sampling adequacy measure based on the Kaiser-Meyer-Olkin (KMO) value is 0.745 (high). The rotated component matrix in test of validity showed the value of all items in the questionnaire are more than 0.30 and each item loaded with its proposed constructs. While, Cronbach’s Alpha values showed the reliability of the items are high (range from 0.681 to 0.870). Descriptive analysis, means and standard deviation was conducted to identify the level of affected factor of household in their pre-cycling, reusing and recycling activities. The highest factor for pre-cycling, reusing and recycling activities of household was social factors. Besides that, their pre-cycling, reusing and recycling behavior was also influenced by economic factor while religious and political factors are the least supporting factors. The findings are useful as a platform in order to advocate consumption ethics amongst Muslim community in Malaysia.